Knowledge, Attitude and Practice of Mothers about Exclusively Breastfeeding in Sabzevar in 2017 - Aghil Keykhosravi; Bita Barghamadi; Rozita Sabzevari; Mohammad Neamatshahi; Mahboubeh Neamatshahi (Mashhad University of Medical Sciences, 2019)
Background: Exclusive breastfeeding is one of the most important issues for public health and Pediatricians in developing countries. Despite the importance of exclusive breastfeeding, only 39% of children in the world are breastfed during the first six months of life. Methods: This study was a Cross-sectional descriptive-analysis conducted on a total number of 396 breastfeeding mothers in 2017.The data collection tool was a structured questionnaire, including demographic information, questions about knowledge and attitude, and performance. We collected the data through face-to-face interview. Results: Based on our results mean and standard deviation of knowledge score of exclusive breastfeeding, attitude, and performance were reported as 7.6±2.4, 43.1±3.3, and 5.1±0.9, respectively. Frequency rates of participants who had high performance, knowledge, and attitude level were, 93.4 % (370), 26 % (103), and 98.5 % (390), respectively. Conclusion: The present study indicated that the majority of mothers had a positive attitude and practice desired however knowledge score was low. Maternal education and relatives was one of the important determinants of exclusive breastfeeding. Health care professionals have important roles in providing suitable fields for these interventions. Using open and extensive questions in other studies can help in finding the causes of breastfeeding cessation during infancy.